2019
DOI: 10.1177/0272989x19861963
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Decision Making for Biopsies in Prostate Cancer Active Surveillance Programs

Abstract: Background. Low-risk prostate cancer patients enrolled in active surveillance programs commonly undergo biopsies for examination of cancer progression. Biopsies are conducted as per a fixed and frequent schedule (e.g., annual biopsies). Since biopsies are burdensome, patients do not always comply with the schedule, which increases the risk of delayed detection of cancer progression. Objective. Our aim is to better balance the number of biopsies (burden) and the delay in detection of cancer progression (less is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Finally, dynamic risk prediction techniques incorporated into active surveillance management strategies will help in finding the optimal balance between the burden of monitoring while on active surveillance and the risk of missing signs of disease progression. The first models show encouraging results and the time has come to prospectively validate this approach (19)(20)(21)(22).…”
Section: Editorial Commentarymentioning
confidence: 97%
“…Finally, dynamic risk prediction techniques incorporated into active surveillance management strategies will help in finding the optimal balance between the burden of monitoring while on active surveillance and the risk of missing signs of disease progression. The first models show encouraging results and the time has come to prospectively validate this approach (19)(20)(21)(22).…”
Section: Editorial Commentarymentioning
confidence: 97%
“…We used a Bayesian joint modelling contemporary approach, 8 which is optimal for integrating longitudinal parameters recorded at any time intervals, and prognostic factors that do not vary over time. This approach has already been found to have clinical relevance in several health domains, such as oncology, 9 cardiovascular disease, 10 and hypertension. 11…”
Section: Introductionmentioning
confidence: 99%
“…In other words, longer delays in detecting upgrading may be acceptable after the first negative biopsy. To evaluate the potential harm of personalised schedules, we compared them with fixed schedules in a realistic and extensive simulation study [32]. We concluded that personalised schedules plan, on average, six fewer biopsies compared to annual schedule and two fewer biopsies than the PRIAS schedule in slow/non-progressing AS patients, while maintaining almost the same time delay in detecting upgrading as the PRIAS schedule.…”
Section: Discussionmentioning
confidence: 99%
“…A caveat of doing so is that reduction in the number of PSA measurements can also lead to an increase in the variance of risk estimates, and also affect the performance of personalised schedules. Although we have done a simulation study to conclude that personalised schedules may not be any more harmful than PRIAS or an annual schedule [32], with an infrequent PSA schedule, these conclusions may not hold. Hence, we do not recommend any changes in the schedule of PSA measurements from the current protocol of PSA measurements every 6 months.…”
Section: Discussionmentioning
confidence: 99%